Relationship between the age related performance of a typical bituminous binder in South Africa and the fatigue performance of the asphalt mixture - Van Zyl, Stiaan (Stellenbosch : Stellenbosch University, 2018)
Thesis (MEng)--Stellenbosch University, 2018.